Effect of building design on maintenance cost / Mohd Khalil Mohd Sojik - Mohd Sojik, Mohd Khalil (Faculty of Architecture, Planning and Surveying, 2009)
The degree to which the design of a building embraces maintenance considerations has a major impact on its performance. Various problem arise during the building was use but, only few are aware of the importance to consider maintenance factors during design stage. A survey was carried out on four building maintenance company. The aim was to find out the building defects and other maintenance problems that are heavily attributed to design deficiencies, inadequate information gathering, material limitations and lack of maintenance knowledge. Findings show that main problems that the maintenance firms are currently facing are caused by building design deficiencies, poor construction quality and poor performance of building which is directly related to functional layout, choice of building material and choice of building equipment. It appears that designer firms consider maintenance factors like ease of cleaning, access to cleaning area and repair and replacement to be the least important when designing buildings.